An ultra-fast, one-step RNA amplification method for the detection of Salmonella in seafood. Issue 11 (25th February 2022) - Zhao, Xiaoli; Zhang, Jian; Duan, Yake; Wan, Qianyi; Zhang, Xin; Chen, Jiao; Shi, Chao; Gao, Yan; Ma, Cuiping
Abstract : Salmonella is one of the most common pathogens associated with food-borne illness resulting from seafood consumption. Abstract : Salmonella is one of the most common pathogens associated with food-borne illness resulting from seafood consumption. Herein, an accelerated strand exchange amplification (ASEA) requiring only a pair of primers and one polymerase was first reported for ultra-fast, one-step RNA amplification detection of Salmonella in seafood. The ASEA method could detect Salmonella typhimurium DNA in dilutions as low as 10 copies per reaction and displayed good specificity for Salmonella under the interference of a variety of food-borne pathogens. In particular, ASEA could detect RNA in one step without additional reverse transcription. The detection limit for Salmonella in artificially contaminated oyster was 1 CFU mL −1 following 12 h of enrichment. Moreover, excellent performance of this assay was observed with 99.02% consistency relative to real-time PCR through actual sample detection. Combined with the rapid nucleic acid extraction method, the entire detection process could be completed within 20 min. Therefore, this assay opens up new prospects for the detection of food-borne pathogens in seafood with its rapidity, which would be very beneficial for food safety supervision and pathogen detection of high-throughput samples.